Effects of a competitive half-season on the aerobic capacity and match running performance of Turkish elite professional soccer players - Akyildiz, Zeki; Guler, Aytek Hikmet; Cene, Erhan; Palucci Vieira, Luiz H.; Aquino, Rodrigo; Clemente, Filipe Manuel (SAGE PUBLICATIONS LTD, 2025)
This study examines how exertion during matches affects participants' physical capacity and match performance. The study included 13 elite football league players (21 +/- 0.7 years old; height, 181.1 +/- 8.98 cm; body mass, 74.7 +/- 8.1 kg) and used global positioning system (GPS) data collected during 12 official matches. Four matches after the first Yo-Yo IR1 test, four matches before the second Yo-Yo IR1 test, and four matches after the second Yo-Yo IR1 test are examined. Sprint count per minute (SC) (N/min), (>19 km/h), p < 0.030; distance covered at zone 4-6 per minute DCZ4 (km/h/min), (18-24 km/h), p < 0.00; distance covered at zone 4-6 per minute DCZ5 (km/h/min), (24-30 km/h), p < 0.001; and distance covered at zone 4-6 per minute DCZ6 (km/h/min), (30-39 km/h), p < 0.001 were recorded. According to the values obtained before the tests, the match data show a decreasing trend in the following weeks. Furthermore, the relationship between physical performance values and tests is determined (average speed (AS) (km/h), r = 0.64; maximum speed (MS) (km/h), r = 0.50; DCZ4 (km/h/min), r = 0.89; DCZ5 (km/h), r = 0.81). As a result, time-dependent changes in intermittent endurance capacity during matches validated in-game running kinematics. This indicates the Yo-Yo IR1's robustness as a fitness marker, and its capacity to help practitioners preview longitudinal variations in locomotor behavior during matches. Athletes who show a high degree of asymmetry in official matches seem to exhibit a strong ability to resist fatigue during testing.
Keywords: Match analysis; Yo-Yo IR1; GPS; aerobic fitness; training; testing; soccer; football; professional soccer; elite soccer; athlete tracking technology; INTERMITTENT RECOVERY TEST; RELIABILITY; FITNESS; SPEED; PERIODIZATION; ENDURANCE; VALIDITY; GAMES; Engineering; Sport Sciences